2008
DOI: 10.1210/me.2006-0534
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Testicular Steroid and Cholesterol Homeostasis

Abstract: The male sex steroid, testosterone (T), is synthesized from cholesterol in the testicular Leydig cell under control of the pituitary gonadotropin LH. Unlike most cells that use cholesterol primarily for membrane synthesis, steroidogenic cells have additional requirements for cholesterol, because it is the essential precursor for all steroid hormones. Little is known about how Leydig cells satisfy their specialized cholesterol requirements for steroid synthesis. We show that in mice with a unique hypomorphic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 38 publications
3
56
1
1
Order By: Relevance
“…The finding of no change in the SREBP2-targeted HMGCR gene expression at the mRNA level (Fig. 3) supports early studies showing the lack of a regulatory role of SREBP2 in cholesterol synthesis in Leydig cells (16). However, the role of SREBP2 in cholesterol formation in Leydig cells require further studies, and the GRTH Ϫ/Ϫ model may be appropriate for this purpose.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The finding of no change in the SREBP2-targeted HMGCR gene expression at the mRNA level (Fig. 3) supports early studies showing the lack of a regulatory role of SREBP2 in cholesterol synthesis in Leydig cells (16). However, the role of SREBP2 in cholesterol formation in Leydig cells require further studies, and the GRTH Ϫ/Ϫ model may be appropriate for this purpose.…”
Section: Discussionsupporting
confidence: 80%
“…Although SREBP2 as a transcription factor is known to activate genes involved in the cholesterol biosynthetic pathway and receptor-mediated cholesterol uptake (17) in most mammalian cells, this may not be the case for gonadal steroidogenesis. Studies in mouse Leydig cells revealed that cAMP-stimulated expression of genes involved in cholesterol synthesis is independent of the nuclear recruitment of SREBP2 (16). In the case of GRTH null mice, the significantly up-regulated SREBP2 expression (Figs.…”
Section: Discussionmentioning
confidence: 94%
“…cAMP elevation and PKA activation are known to stimulate several critical steps in steroid production (42). PKA activation leads to activation of HSL (5,43), which releases cholesterol and free fatty acids from cholesteryl ester storage and perhaps other sites in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Hypophysectomy results in decreased CYP17A1 expression, but the levels were increased by treatment with exogenous LH but not FSH (Takeyama et al, 1986). The molecular basis by which LH induced CYP1B1 protein levels is not clear at this time, but it may involve LH receptor activation and increased intracellular levels of cAMP, which is the mechanism by which LH increases expression of genes encoding P450 enzymes involved in androgen synthesis (Eacker et al, 2008).…”
Section: Leung Et Almentioning
confidence: 99%
“…Testosterone acting through the androgen receptor is needed for normal development of the testis (Haider, 2004). Previous studies showed that treatment of intact rats with high dosages of testosterone reduces LH secretion from the pituitary, represses transcription of genes involved in steroidogenesis, including CYP17A1 and CYP11A1, and inhibits spermatogenesis (Keeney and Ewing, 1990;Eacker et al, 2008). Treatment of adult hypophysectomized rats with testosterone can partially restore spermatogenesis, but it had little effect on Leydig cell proliferation or function (Keeney and Ewing, 1990).…”
Section: Leung Et Almentioning
confidence: 99%